2019
DOI: 10.1002/jper.18-0639
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent parathyroid hormone promotes cementogenesis in a PKA‐ and ERK1/2‐dependent manner

Abstract: Background: Intermittent parathyroid hormone (PTH) promotes cementogenesis and provides a promising biotherapeutic to rehabilitate resorbed roots. However, the underlying mechanisms remain inconclusive. Cyclic aenosine monophosphate (AMP)-dependent protein kinases A (PKA) and extracellular signal-regulated MAP kinases 1/2 (ERK1/2) are key regulators of bone remodeling. The present study aims to investigate whether PKA and ERK1/2 are involved in the process of intermittent PTH-promoted cementogenesis.Methods: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
2
22
1
Order By: Relevance
“…PTH exerts anabolic effects on cementum formation of developing teeth in young rats and these effects were also confirmed by in vitro studies (Y. Li et al, 2017;Silva, Vasconcelos, Marques, & Barros, 2016;Xu et al, 2019). Taken together, these findings strongly support that intermittent PTH administration does have the capacity for promoting the anabolic activity of cementoblasts and facilitating the healing process of OIRR.…”
Section: Intermittent Pth Promoted Cementogenesis Of Occm-30 Cells supporting
confidence: 64%
See 1 more Smart Citation
“…PTH exerts anabolic effects on cementum formation of developing teeth in young rats and these effects were also confirmed by in vitro studies (Y. Li et al, 2017;Silva, Vasconcelos, Marques, & Barros, 2016;Xu et al, 2019). Taken together, these findings strongly support that intermittent PTH administration does have the capacity for promoting the anabolic activity of cementoblasts and facilitating the healing process of OIRR.…”
Section: Intermittent Pth Promoted Cementogenesis Of Occm-30 Cells supporting
confidence: 64%
“…Western blots were performed as described previously (Hu et al, 2018;Xu et al, 2019). The primary antibodies used in this study were EPHB4…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Results showed that high dose of iPTH may counteract part of the inhibition effects of BMS‐536924. As shown by previous studies, iPTH may exert its biological effects through else signaling pathways other than IGF‐1 (Xu et al., 2019). Even so, the mineralization activities of high PTH + inhibitor groups were still significantly weaker than the PTH group.…”
Section: Discussionmentioning
confidence: 66%
“…Then, the animals were randomly divided into 2 groups of 24 animals each: the PTH group and the control group. From the first day of maintenance phase, the animals in the experimental group received a daily injection of PTH (1–34) (Bachem) at a dosage of 4 mg per 100 g of body weight, while the control group received the same volume of vehicle (0.1% acetic acid; Li et al., 2013; Xu et al., 2019). After 4 weeks, the orthodontic wires were detached and maxillary first molars endured a relapsing phase for 2 weeks (Figure 1c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation